CN-assisted oxidative cyclization of cyano cinnamates and styrene derivatives: a facile entry to 3-substituted chiral phthalides - Reddy, R. Santhosh; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2012)
The asymmetric dihydroxylation (AD) of o-cyano cinnamates and styrene derivatives leads to efficient construction of chiral phthalide frameworks in high optical purities. This unique reaction is characterized by unusual synergism between CN and osmate groups resulting in rate enhancement of the AD process. The method is amply demonstrated by the synthesis and the structural/stereochemical assignment of the natural products.